EFFECT OF PREGNANCY ON BODY HAIR GROWTH IN DAIRY CATTLE - S. Khan; N. Ishikawa; T. Hattori; A. Tajima; M. S. Qureshi (Journal of Animal and Plant Sciences, 2012)
Pregnancy is a dynamic state associated with a number of hormonal changes. Present study reports the effect of pregnancy and parturition on body hair growth in dairy cattle. For this purpose Holstein Friesian cows, three early pregnant and two post-parturition were used. The hairs samples from neck, thoracic and back areas were collected twice a week for a period of two months to measure hair weight and the diameter. An increase in hair diameter and weight with advancing days of pregnancy was observed, whereas the hair weight decreased after parturition. In pregnant cows, a persistent increase of diameter and weight along the individual fibers from tip to end was observed. Furthermore, a similar pattern of increase in weight and diameters was also observed for the neck thoracic and back hairs. A positive and significant correlation between hair fiber diameter and weight was observed in pregnant cows. These results indicated that the hair growth is affected by the pregnancy status in dairy cattle.
Keywords: Pregnancy; body hair; hair diameter; fiber weight and dairy cattle